Endovascular Aneurysm Sealing Is Associated With Reduced Radiation Exposure and Procedure Time Compared With Standard Endovascular Aneurysm Repair. (April 2016) - Antoniou, George A.; Senior, Yashika; Iazzolino, Luigi; England, Andrew; McWilliams, Richard G.; Fisher, Robert K.; Torella, Francesco
Purpose: To compare indirect measures of radiation exposure and operating time between endovascular aneurysm sealing (EVAS) and endovascular aneurysm repair (EVAR) for the treatment of abdominal aortic aneurysm (AAA).Methods: The study compared 32 consecutive patients (mean age 78 years; 21 men) with AAA who underwent standard EVAS with 32 consecutive patients (mean age 78 years; 25 men) treated with EVAR between November 2013 and May 2015. Electronic medical records and image archiving databases were interrogated to retrieve relevant information and scans. Screening time and dose area product (DAP) were the primary outcome measures. Data are presented as median and interquartile range (IQR). Correlations were tested with the Spearman rank coefficient (ρ).Results: The screening time was shorter in EVAS than in EVAR [16 (IQR 14, 20) vs 32 (IQR 26, 38) minutes; p<0.001]. DAP was lower in EVAS than in EVAR [54 (IQR 42, 77) vs 111 (IQR 75, 157) Gy∙cm 2 ; p<0.001]. Digital subtraction angiography delivered 20% (IQR 15%, 28%) of the DAP in EVAS compared with 14% (IQR 11%, 19%) in EVAR (p<0.001), but the absolute time used on digital subtraction was marginally lower in EVAS than in EVAR [1.07 (IQR 0.52, 1.23) vs 1.19 (IQR 0.70, 1.39) minutes; p=0.037]. The operating time was shorter for EVAS [121 (IQR 105, 146) vs 162 (IQR 145, 186) minutes; p<0.001]. There was a moderate correlation between DAP and screening time (ρ=0.597, p<0.001), fluoroscopy time (ρ=0.595, p<0.001), digital subtraction time (ρ=0.301, p=0.015), and operating time (ρ=0.512, p<0.001).Conclusion: EVAS is associated with reduced radiation exposure and operating room usage compared with EVAR, which may have safety and financial implications.